2008
DOI: 10.1302/0301-620x.90b11.21163
|View full text |Cite
|
Sign up to set email alerts
|

The epidemiology of fractures in adolescents with reference to social deprivation

Abstract: A relationship between social deprivation and the incidence of fracture in adolescents has not previously been shown. We have used a complete fracture database to identify adolescents who sustained fractures in 2000. The 2001 Scottish census was used to obtain age-specific population and deprivation data according to the Carstairs score. Regression analysis determined the relationship between the incidence of fractures and social deprivation. We analysed 1574 adolescents with fractures (1083 male, 491 female).… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
32
2

Year Published

2010
2010
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 49 publications
(36 citation statements)
references
References 14 publications
2
32
2
Order By: Relevance
“…In some reports, all the patients going to a medical center were studied, while, some other studies, including the present study, examined the hospitalized patients with severe traumas (Urquhart et al, 2006). Moreover, the location of a specific medical center, different seasons of the year, racial differences, the level of welfare in different populations and countries influence the number of traumatic patients (Menon et al, 2008;Amin et al, 2011;Donaldson et al, 1990;Koo et al, 2013). …”
Section: Discussionmentioning
confidence: 88%
See 1 more Smart Citation
“…In some reports, all the patients going to a medical center were studied, while, some other studies, including the present study, examined the hospitalized patients with severe traumas (Urquhart et al, 2006). Moreover, the location of a specific medical center, different seasons of the year, racial differences, the level of welfare in different populations and countries influence the number of traumatic patients (Menon et al, 2008;Amin et al, 2011;Donaldson et al, 1990;Koo et al, 2013). …”
Section: Discussionmentioning
confidence: 88%
“…Although the importance of the subject is clear, there are few epidemiological studies appropriate for quantitative and qualitative evaluation of such injuries in different societies (Urquhart et al, 2006;Court-Brown & Caesar, 2006;Menon et al, 2008;Amin et al, 2014). Moreover, the epidemiology of such injuries differs from one society to another, and cannot be generalized (Scholes et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…There is a progressive increase in the number of fractures with age in the paediatric population [12,19]. In our series, we noticed that 60% of the children in the outpatient and 50% of the inpatient study group were between 11 and 15 years old.…”
Section: Discussionmentioning
confidence: 50%
“…Population-based studies from Scotland found that children living in deprived areas have higher fracture rates than those from affluent areas [19,24]. In contrast, a similar study from South Wales did not show any correlation [14].…”
Section: Discussionmentioning
confidence: 83%
“…The Carstairs score is a -score based on overcrowding, male unemployment, social class, and car ownership. It has been extensively used to examine social deprivation in orthopaedic surgery [7,8,12] and other branches of medicine [9,13]. The Carstairs score can be used to divide the population of Scotland into five equal quintiles, with Quintile 1 (Q1) being the most affluent and Quintile 5 (Q5) being the most deprived.…”
Section: Methodsmentioning
confidence: 99%